A Randomized Clinical Trial of Berberine Hydrochloride in Patients with Diarrhea‐Predominant Irritable Bowel Syndrome. (24th September 2015) - Chen, Chunqiu; Tao, Chunhua; Liu, Zhongchen; Lu, Meiling; Pan, Qiuhui; Zheng, Lijun; Li, Qing; Song, Zhenshun; Fichna, Jakub
Abstract : We aimed to evaluate clinical symptoms in diarrhea predominant irritable bowel syndrome (IBS‐D) receiving berberine hydrochloride in a randomized double‐blind placebo‐controlled clinical trial. Overall, 196 patients with IBS‐D were recruited for this study; consequently, 132 patients randomized to receive daily 400 mg of berberine hydrochloride, delivered twice daily or placebo for 8 weeks followed by a 4‐week washout period. After a 2‐week run‐in period, diarrhea, abdominal pain, urgent need for defecation frequency and any adverse events were recorded daily. Prior to administration of the medication and after completing the treatment, assessment of IBS symptom scores, depression and anxiety scale scores and the IBS scale for quality of life (QOL) was carried out. The effects of berberine hydrochloride on IBS‐D, defined by a reduction of diarrhea frequency ( P = 0.032), abdominal pain frequency ( P < 0.01) and urgent need for defecation frequency ( P < 0.01), were significantly more pronounced in the berberine group than the placebo group in the 8 weeks of treatment. A trend of improvement ( P < 0.05) was observed with berberine hydrochloride for IBS symptom score, depression score and anxiety score and the IBSQOL, compared with placebo. At last, berberine hydrochloride was well tolerated. So we concluded that berberine hydrochloride is well tolerated and reduces IBS‐D symptoms, which effectively improved patients QOL. Copyright © 2015 John Wiley & Sons, Ltd.